Electroforming-free threshold switching of NbOx–based selector devices by controlling conducting phases in the NbOx layer for the application to crossbar array architectures. Issue 29 (23rd June 2022) - Park, Kitae; Ryu, Jiyeon; Sahu, Dwipak Prasad; Kim, Hyun-Mi; Yoon, Tae-Sik
Abstract : A NbO x layer features forming-free bipolar threshold switching for the application to selector devices in crossbar array architectures through controlling conducting phases in the layer by precise deposition and interaction with a niobium electrode. Abstract : Bipolar threshold switching characteristics, featuring volatile transition between the high-resistance state (HRS) at lower voltage than threshold voltage ( V th ) and the low-resistance state (LRS) at higher voltage irrespective of the voltage polarity, are investigated in the Nb(O)/NbO x /Nb(O) devices with respect to deposition and post-annealing conditions of NbO x layers. The device with NbO x deposited by reactive sputtering with 12% of O2 gas mixed in Ar shows threshold switching behaviors after electroforming operation at around +4 V of forming voltage ( V f ). On the other hand, electroforming-free threshold switching is achieved from the device with NbO x deposited in the reduced fraction of 7% of O2 gas and subsequently annealed at 250 °C in vacuum, thanks to the increase of the amount of conducting phases within the NbO x layer. Threshold switching is thought to be driven by the formation of a temporally percolated filament composed of conducting NbO and NbO2 phases in the NbO x layer, which were formed as a result of the interaction with Nb electrodes such as oxygen ion migration either by annealing or electrical biasing. The presence of a substantial amount of oxygen in the Nb electrodes up to ∼40 at%, named Nb(O) herein, would alleviate excessive migration of oxygen and consequent overgrowth of the filament during operation, thus enabling reliable threshold switching. These results demonstrate a viable route to realize electroforming-free threshold switching in the Nb(O)/NbO x /Nb(O) devices by controlling the contents of conducting phases in the NbO x layer for the application to selector devices in high-density crossbar memory and synapse array architectures.